REGULATION OF TRAFFIC TO THE CITY CENTRE BASED ON URBAN ELECTRONIC TOLL (Perner's Contacts, 2019)
This paper deals with traffic regulation in selected city centres based on urban electronic toll. The first chapter of the paper focuses on the reasons for the introduction of urban electronic toll. The second chapter of the paper focuses on the main objectives of the toll system. The third chapter of the paper focuses on technologies of the urban electronic toll system, which are currently used. The fourth chapter of the paper focuses on specific systems of urban electronic toll in selected cities. The aim of the paper is to point out the possibility of reducing the emission burden in the city centre and increasing air quality in cities by introducing regulation of traffic to the city centre by means of urban electronic tolls.
Keywords: traffic regulation; city centre; toll collection